Characteristics of the rotation and flight trajectory of balls thrown by elite female softball pitchers - Morishita, Y.; Murata, M. (Journal of High Performance Sport, 2020)
In this study, we investigated the kinematic characteristics of various pitch types thrown by skilled softball pitchers. Nine female softball pitchers from the national Japanese softball team were requested to throw various pitch types that are used in competition and practice using the windmill style, while a three-dimensional motion capture system consisting of 20 infrared cameras (500 Hz) recorded reflective markers attached to the ball. The kinematic characteristics, such as the ball speed, spin rate, and direction of spin axis (angular velocity vector) were calculated from the measured coordinate values. The types of pitches (fastball, riseball, drop, and changeup) thrown by more than 5 pitchers were analyzed. The spin axes of all the analyzed trials were mostly oriented in the direction of the ball and upwards. The average ball speed of the fastball pitched by all pitchers had the highest, and in the case of the right-handed pitcher, the displacement of flight trajectory on the home plate changed by approximately 0.17 m downward and 0.06 m toward the left-handed batter under the influence of the lift force, as compared to that of the balls that were projected without rotation. Furthermore, when the flight trajectories of other pitch types were compared with that of fastball, the riseball, drop, and changeup types were shown to change in the upward, downward, and upper left directions, respectively. Our findings can be used as a guide to develop new pitch types or improve those that are currently employed in the game.